The Prehistory of Human Migration - Human Expansion, Resource Use, and Mortuary Practice in Maritime Asia - Ono, Rintaro (Archīum Ateneo, 2024)
The Prehistory of Human Migration - Human Expansion, Resource Use, and Mortuary Practice in Maritime Asia presents the current state of archaeological research on the migration and expansion of the first modern humans (Homo sapiens) into the maritime regions of Asia and Oceania. This area, which stretches geographically from the North and Southeast Asian mainland through the archipelagos of Japan, the Philippines, and Indonesia all the way to Oceania, has provided us with numerous new insights and discoveries based on data from archaeological and bioanthropological research, thus revealing the cognitive abilities as well as the behavioural adaptations and technological innovations of these early islanders and seafarers that led to the successful colonization of this unique island world. In seven chapters devoted to the themes ‘Modern Human Migration to Maritime Asia and Oceania’, ‘Modern Human Migration, Technology and Resource Use in Maritime Asia’, and ‘Modern Human Migration and Mortuary Practices in Maritime Asia’, leading archaeologists present their research in Wallacea, the Ryukyu Islands (East Asia), and the coastal regions of Southeast and Northeast Asia, and discuss their findings on early modern human migration to Maritime Asia, the utilization of its diverse resources, and the belief systems of these early islanders during the Late Pleistocene.